Incidence of thrombocytopenia in the neonatal intensive care unit - Gupta, Aparajita (Med J Armed Forces India, 2011)
BACKGROUND: Thrombocytopenia is the commonest haematological abnormality encountered in the neonatal intensive care unit (NICU). The incidence in neonates varies greatly, depending upon the population studied. The aim of the present study was to study the incidence of thrombocytopenia in the neonates admitted to the NICU. METHOD: The study was carried out in 258 consecutive eligible neonates from August 2007 to August 2009. Neonates were placed in two risk groups for thrombocytopenia, viz. high risk and low risk, depending upon the presentation, maternal history and any antenatal/perinatal events. Platelet counts were done on the first, third and fifth day of admission and thereafter every 72 hours till counts were normal. Low counts were collaborated with a peripheral blood smear. RESULTS AND CONCLUSION: The overall incidence of thrombocytopenia in the study group was 70% (182/258). The incidence in the high-risk group was 93.7% cases (134/143) and in the low-risk group was 41.7% (48/115). This difference was statistically significant. Factors associated with thrombocytopenia were sepsis, extreme low birth weight, intra-uterine growth restriction, birth asphyxia and pre-eclampsia in mothers. The most common severe bleeding manifestation was pulmonary haemorrhage. The overall mortality in babies with thrombocytopenia was 33% despite > 90% of these cases having received platelet transfusion. Of these pulmonary haemorrhage was the main cause of death in five cases. It is concluded that thrombocytopenia is very common in the NICU and should be actively looked for so that it can be managed appropriately.